(untitled) (Indian Journal of Arid Horticulture, 2016)
Onion (Allium cepa L.) is a leading bulb vegetable crop from the Alliaceae family, widely grown for its culinary and medicinal values. India ranks second in global onion production, contributing 11.9% to the total vegetable production worldwide, with a productivity of 16.10 q/ha. The continuous use of inorganic fertilizers has led to micronutrient deficiencies, imbalances in soil physico-chemical properties, and unsustainable crop production. Integrated nutrient management offers a viable strategy by combining chemical fertilizers with organic manures for more judicious and efficient use. Both organically and inorganically fertilized onion plants show significantly higher NPK and S content in bulbs compared to unfertilized plants. Nutrient management is crucial for enhancing onion quality. There is limited information on the balanced use of chemical fertilizers and organic manures and their combinations on onion bulb production. This study aims to evaluate the effects of organic manures, fertilizers, and sulfur on the growth, yield, and quality of onion under Bikaner conditions.